One Pot Aqueous Synthesis of L-Histidine Amino Acid Capped Mn: ZnS Quantum Dots for Dopamine Sensing - Arunan, Ravi; Joseph, Printo; Sivakumar, Muthusamy; Kiruba Daniel, Suthanthira C. G. (Current Nanoscience, 2020)
Background: Mn doped ZnS is selected as the right element which is prominent among quantum dot for its high luminescent and quantum yield property and also non toxicity while comparing with other organometallic quantum dot synthesized by using different capping agents. Methods: An interesting observation based on colorimetric sensing of dopamine using manganese doped zinc sulfide quantum dot is discussed in this study. Mn doped ZnS quantum dot surface passivated with capping agents such as L-histidine and also in polymers like chitosan, PVA and PVP were studied and compared. The tunable fluorescence effect was also observed in different polymers and amino acid as capping agents. Optical characterization studies like UV-Visible spectroscopy and PL spectroscopy have been carried out. The functional group modification of Quantum dot has been analyzed using FTIR and size and shape analysis was conducted by using HRTEM image. Results: The strong and broad peak of FTIR in the range of 3500-3300 cm-1 confirms the presence of O-H bond. It is also observed that quenching phenomena in the luminescent peak are due to weaker confinement effect. The average size of the particle is shown to be around 4-5 nm. Changes in color of the quantum dot solution from transparent to dark brown has been due to the interaction with dopamine. Conclusion: Finally, L-Histidine amino acid capped Mn:ZnS shows better results in luminescence and size confinement properties. Hence, it was chosen for dopamine sensing due to its colloidal nature and inborn affinity towards dopamine, a neurotransmitter which is essential for early diagnosis of neural diseases.
Keywords: fluorescence